DIATOM SPECIES COMPOSITION AND THEIR SEASONAL DYNAMICS IN THE TIMOK RIVER BASIN - Đukic, Nikola; Jakšić, Tatjana; Papović, Olivera; Vasić, Predrag (Bulletin of Natural Sciences Research, 2021)
The aim of this paper was to present the composition and seasonal dynamics of epilthic diatoms in the Timok River basin. The diatom samples were collected along the Timok River basin in March, May, August and November 2017. Permanent diatom slides were prepared after oxidizing the organic material by the hydrogen peroxide (H2O2). The cleaned diatom materials were mounted on permanent slides using ZRAX glue. A total of 85 taxa were identified in the Timok River Basin. The benthic diatom taxa belong to 31 genera with the highest diversity observed within Navicula Bory (15), Nitzschia Hassall (12) and Gomphonema Ehrenberg (8). Quantitative analysis showed that in all seasons, Achnanthidium  minutissimum and Amphora pediculus were dominant taxa. In May, they were joined by the Achnanthidium  pyrenaicum, Gomphonema olivaceum and Ulnaria ulna; in August by the Cocconeis placentula, Denticula kuetzingii, Melosira varians, Navicula metareichardtiana, Nitzschia capitellata, N. fonticola and N. palea; in November by the D.  kuetzingii, G. olivaceum, G.  pumilum, N. metareichardtiana, N. veneta, Nitzschia capitellata and N. palea and in March by A. pyrenaicum, Diatoma moniliformis, G. olivaceum, N. palea and U. ulna. Our research is the floristical and ecological study of benthic diatoms in this basin and can form the groundwork for further research work.
Keywords: Benthic diatoms; Species composition; Seasonal dynamics; Ecology; Timok River